The beginnings of the Order of Saint John in Jerusalem, or: Muristan revisited - Dorothee Heinzelmann; Jürgen Krüger (Medievalista)
The order of Saint John was founded during the 12th century south of the Church of the Holy Sepulchre in Jerusalem in an area known today as Muristan. The heart of the order's residence was the once famous hospital, which was the origin of numerous pilgrim hostels and hospitals throughout Europe. Given its historical significance, it is surprising how little is known about this building complex. Through pilgrims' reports and statutes of the order, the functioning of the hospital is relatively well known. But as a result of later changes and destruction only a few remnants of the medieval building stock have survived and are largely unexplored until today.In an interdisciplinary research project the development of the Muristan from antiquity to modern times is being investigated. Archival records are being re-evaluated, preserved and accessible architectural remains are documented and analysed by methods of building archaeology. This article presents some results of the project on the medieval development of the Muristan and the seat and hospital of the Order of St. John.